p.Gln318X and p.Val281Leu as the Major Variants of CYP21A2 Gene in Children with Idiopathic Premature Pubarche - Mahdieh Soveizi; Nejat Mahdieh; Aria Setoodeh; Fatemeh Sayarifard; Farzaneh Abbasi; Himangshu S. Bose; Bahareh Rabbani; Ali Rabbani (International Journal of Endocrinology)
Premature pubarche (PP) is the appearance of sexual hair in children before puberty. The PP phenotype may attribute to nonclassic congenital adrenal hyperplasia (NC-CAH). In this study, we investigated the role of CYP21A2 gene variants in patients with PP in the Iranian population. Forty patients (13 males and 27 females), clinically diagnosed with PP, were analyzed for molecular testing of CYP21A2 gene variants. Direct sequencing was performed for the samples. Also, gene dosage analysis was performed for the cases. Fourteen patients (35%) had a mutation of p.Gln318X and p.Val281Leu, out of which 10% had regulatory variants. Approximately 10% of the patients were homozygous (NC-CAH). 78.5% (11/14) of patients had trimodular RCCX of which 5 patients had two copies of CYP21A1P pseudogene. The prevalence of p.Val281Leu was higher than p.Gln318X in PP patients. In conclusion, CYP21A2 variant detection has implications in the genetic diagnosis of PP phenotype. The genetic characterization of the CYP21A2 gene is important for characterizing the variable phenotype of carriers and genetic counseling of PP and NC-CAH patients.